2007
DOI: 10.1161/01.atv.0000253886.44609.ae
|View full text |Cite
|
Sign up to set email alerts
|

Ccr5 But Not Ccr1 Deficiency Reduces Development of Diet-Induced Atherosclerosis in Mice

Abstract: Objective-Chemokines and their receptors are crucially involved in the development of atherosclerotic lesions by directing monocyte and T cell recruitment. The CC-chemokine receptors 1 (CCR1) and 5 (CCR5) expressed on these cells bind chemokines implicated in atherosclerosis, namely CCL5/RANTES. Although general blockade of CCL5 receptors reduces atherosclerosis, specific roles of CCR1 and CCR5 have not been unequivocally determined. Methods and Results-We provide two independent lines of investigation to diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
193
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 251 publications
(207 citation statements)
references
References 40 publications
12
193
1
1
Order By: Relevance
“…29 Braunersreuther et al reported that RANTES plays a central role in promoting late-stage atherosclerosis in the context of accelerated atherosclerosis in ApoE -/-mice promoted by high-fat diet. 30 Fractalkine (CX3CL1) is a unique member of the CX3C chemokine subfamily. Accumulating evidence indicates CX3CL1/ CX3CR1 involvement in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Braunersreuther et al reported that RANTES plays a central role in promoting late-stage atherosclerosis in the context of accelerated atherosclerosis in ApoE -/-mice promoted by high-fat diet. 30 Fractalkine (CX3CL1) is a unique member of the CX3C chemokine subfamily. Accumulating evidence indicates CX3CL1/ CX3CR1 involvement in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the redundancy of chemokine system, we cannot exclude that a chronic anti-chemokine treatment (i.e., Evasin-3) might induce a compensatory upregulation of other chemoattractants or chemokine receptors responsible for macrophage intraplaque recruitment. 26 Another limitation of the present study is represented by the assessment of mouse plaque vulnerability based on histologic surrogate biomarkers, instead of clinical cardiovascular outcomes (i.e., acute cerebral events). Since ApoE À / À mice have been shown to develop accelerated atherogenesis (also associated with microglial inflammation), [27][28][29] but not spontaneous ischemic events in the life time comparable to our shear stress-induced protocol (max 31 weeks of age), we were not able to assess carotid plaque vulnerability on the basis of a clinical thrombotic rupture.…”
Section: Evasin-3 Treatment In Carotid Atherosclerosismentioning
confidence: 99%
“…2 CC-CKs including MCP-1, RANTES and MIP-1a are present in human atherosclerotic lesions. [3][4][5][6] In the atherosclerosis-prone apolipoprotein E knockout (ApoE-KO) mice, targeted deletion of single CC-CKs or CK receptors significantly reduces atherosclerotic plaque progression [7][8][9] demonstrating that a number of different CC-CK/CC-CK receptor interactions are important in atherosclerosis. Indeed, the marked functional redundancy in the CK/CK receptor signalling system suggests that a more broad-spectrum approach to CC-CK signaling may provide a more efficient strategy to reduce atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%